The prognosis of assisted peritoneal dialysis - WANG Ying; WANG Hai-yun; XIA Peng; LIU Bing-yan; ZHOU Zi-juan; CUI Ying; YANG Wei; LIANG Jing; LI Xue-mei; CHEN Li-meng (Linchuang shenzangbing zazhi)
Objective To investigate the effect of assisted peritoneal dialysis(PD)and self-care peritoneal dialysis on the prognosis of PD patients.Methods This retrospective study enrolled 637 adult patients started PD in Peking Union Medical College Hospital(PUMCH)from March 13,1996,to December 31,2016,and their clinical data were collected.Patients were divided into assisted and self-care PD groups according to the independence of manipulation of PD.In the assisted PD group patients were further divided into automated peritonealdialys(APD)and continuous ambulatory peritoneal dialysis(CAPD)groups according to different PD modes.Technique survival,peritonitis-free survival,and patient survival were compared between groups.Results Of the 637 patients,373 patients(35 with APD and 338 with CAPD)needed assistance.Assisted PD patients had older ages,a higher proportion of complications including diabetes,hypertension and cardiovascular diseases,higher levels of serum total carbon dioxide(TCO2)and estimated glomerular filtration rate(eGFR),but lower levels of serum albumin,potassium,phosphorus,creatinine,urea and parathyrin,and normalized protein catabolic rate(nPCR),compared to self-care PD patients.Assisted APD patients had a higher proportion of complications of cardiovascular diseases,a higher proportion of patient care need,and a higher residual kidney function at 3 months after PD initiation,compared to assisted CAPD patients.A worse survival was observed in the assisted PD patients than in the self-care PD ones;however,after multi-factor correction, assisted PD was not the independent risk factor for mortality(HR1.479,95%CI 0.978～2.236,P=0.064).Assisted PD and self-care PD patients had similar technique survival and peritonitis-free survival.Assisted APD and assisted CAPD patients had comparable patient survival,technique survival,and peritonitis-free survival.Conclusions Patient survival is worse in assisted PD patients,compared to self-care PD patients.There is no difference in technique survival and peritonitis-free survival between the two groups.APD patients have comparable patient survival,technique survival and peritonitis-free survival to assisted CAPD ones,and so assisted APD is a viable alternative for patients in need.